TANTANGAN MANAJEMEN PENDIDIKAN ISLAM DALAM MENGHADAPI ERA GLOBALISASI - M. Adlin Manik (UIN Sumatera Utara Medan, 2016)
Management of Islamic education , as a branch of the management , which is a very important function for critics, scholars, and shoots the nation to become a learner as well educator good and moral . The role of educators in criticizing globalization is very important. In fact, in the management of Islamic education should be considered and critical to the global competition. Therefore, the effect of ( bad ) globalization can quickly enter into our lives, into our subconscious, to act like what is desired by the development of globalization . Keyword: management education, globalization, education management solution